Fiber-reinforced modified silicon dioxide aerogel as well as preparation method and application thereof
Through the preparation method of fiber-reinforced modified silica aerogel, the shortcomings of traditional aerogel insulation materials in terms of mechanical strength, bonding performance and construction difficulty are solved, and significantly improved mechanical properties, weather resistance and isolation are achieved. Thermal insulation performance.
Patent Information
- Application Number
- CN202411568424.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-11
AI Technical Summary
The application of traditional silica aerogel in the field of building insulation has problems such as high production costs, reduced macro strength, unsatisfactory bonding performance, complex construction and unsatisfactory insulation effect.
By using fiber-reinforced modified silica aerogel, including acid treatment and surface modification treatment of inorganic fibers, vacuum impregnation and gelation reactions combined with silica sol and modified emulsion, and finally aging and aging The treatment is made to obtain an aerogel thermal insulation coating with significantly improved mechanical properties, weather resistance and thermal insulation properties.
It significantly improves the bonding, mechanical strength, insulation performance and thermal stability of aerogels with other materials, simplifies the construction process, reduces production costs, and achieves efficient thermal insulation effect.
Smart Images

Figure BDA0005119838990000161 
Figure BDA0005119838990000171 
Figure BDA0005119838990000191
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aerogels, and in particular to a fiber-reinforced modified silica aerogel and a preparation method and application thereof. Background Art
[0002] The energy consumption of the construction industry accounts for about 20% of the total energy consumption in the country, and improving the thermal insulation performance of the enclosure structure is one of the effective measures for building energy conservation. In the southern region, the inner side of the exterior walls of residential buildings generally do not take certain insulation measures for the walls, and only use traditional putty for wall leveling and paint beautification; even if thermal insulation measures are taken, the insulation materials generally used are mostly polyurethane foam, thermal insulation mortar, expanded perlite and other materials. These materials are porous and loose, and they are easy to absorb water, crack, and even fall off during use. Not only is the construction complicated, but it is also impossible to keep consistent with the life of the wall. Based on the above factors, in terms of energy conservation and emission reduction in the construction industry, it is urgent to develop new, high-performance, lightweight thermal insulation materials for the interior walls of buildings.
[0003] Silica aerogel is a lightweight porous material composed of SiO2 molecules with a three-dimensional nano-space grid structure and has an extremely low density (0.0030 g / cm 3 ), ultra-high porosity, more than 500m 2 / g specific surface area, lower thermal conductivity than air (0.0267W / (m·K)), strong thermal stability, low dielectric constant, extremely small average pore size (2.00nm~50.00nm) and other excellent properties make it an ideal thermal insulation material. It has been widely used in building thermal insulation, industrial thermal insulation, new energy vehicles, environmental protection and other fields. However, the preparation process of pure silica aerogel is complicated, and the porous and loose structure of aerogel leads to extremely poor macroscopic mechanical properties, which are brittle and fragile, making it difficult to use it alone as a thermal insulation material. In addition, the traditional silica aerogel production process is complicated and the cost of raw materials is high, which greatly limits its application in the construction field.
[0004] The existing technology achieves the enhancement of the strength of silica aerogel through modification, especially improving its brittle characteristics. For example, glass fiber material is introduced into the gel, so that the silica aerogel is attached to the glass fiber skeleton structure, which plays a supporting and protective role, improves the compressive performance, and hinders the transmission of micro cracks. However, since traditional glass fibers are all micron-sized, they cannot effectively enhance the porous grid structure of aerogels at the nanoscale, and still cannot significantly improve its brittleness; even if nano-scale glass fibers are used as reinforcements, since they are only physical and mechanical combinations, the improvement of macroscopic mechanical properties is still relatively limited.
[0005] In order to further solve the application defects of silica aerogel in the field of building insulation, a series of aerogel composite thermal insulation materials such as aerogel insulation mortar and aerogel insulation felt have appeared on the market. Although such materials have good thermal insulation properties, they do not fundamentally solve the defects of low bonding strength with other materials due to the smooth surface of aerogel and decreased macroscopic strength of composite materials after the addition of aerogel. Not only are the installation and construction complicated and the price high, but there are also problems such as high water absorption, easy to fall off, and thermal insulation effect not meeting expectations.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The first purpose of the present invention is to provide a method for preparing fiber-reinforced modified silica aerogel, so as to comprehensively solve the pain points of traditional aerogel thermal insulation building materials that are difficult to simultaneously meet high standards in terms of mechanical strength, bonding performance, thermal insulation effect, construction difficulty, cost, etc.
[0008] The second object of the present invention is to provide a fiber-reinforced modified silica aerogel.
[0009] The third object of the present invention is to provide an aerogel thermal insulation coating having significantly improved mechanical properties, weather resistance and thermal insulation properties.
[0010] The fourth object of the present invention is to provide a method for preparing the aerogel thermal insulation coating, which is simple, convenient and easy to mass produce.
[0011] The fifth object of the present invention is to provide use of the aerogel thermal insulation coating in building materials.
[0012] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0013] A method for preparing fiber-reinforced modified silica aerogel comprises the following steps:
[0014] (1) treating the inorganic fiber with acid and performing surface modification treatment in sequence to obtain hydroxylated modified fiber;
[0015] (2) mixing silica sol, the hydroxylated modified fiber and a modified latex, and then sequentially performing vacuum impregnation treatment and gelation reaction to obtain a modified silica gel; wherein the modified latex comprises acrylic acid, an acrylate compound and a persulfate;
[0016] (3) The modified silica gel is aged and aged, and then replaced with an alcohol solution and dried to obtain a fiber-reinforced modified silica aerogel.
[0017] A fiber-reinforced modified silica aerogel is prepared by the fiber-reinforced modified silica aerogel preparation method.
[0018] An aerogel heat-insulating coating comprises the fiber-reinforced modified silica aerogel.
[0019] A method for preparing the aerogel thermal insulation coating comprises the following steps:
[0020] The fiber-reinforced modified silica aerogel, aqueous film-forming agent, filler, dispersant and defoamer are fully mixed to obtain the aerogel thermal insulation coating.
[0021] A use of the aerogel thermal insulation coating in building materials.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) In order to solve the many defects of traditional silica aerogel building insulation products, such as high production cost, significant decrease in macroscopic strength after adding aerogel, unsatisfactory bonding performance, complex construction, and unsatisfactory insulation effect, the present invention proposes a fiber-reinforced modified silica aerogel, which adopts a secondary modification method for inorganic fibers to significantly improve the bonding between aerogel and other materials, increase its mechanical strength, thermal insulation performance and thermal stability.
[0024] (2) The present invention optimizes the selection of raw material combinations and adjusts the ratio end to obtain an aerogel thermal insulation coating, which can significantly enhance the mechanical properties, weather resistance and thermal insulation properties of silica coatings. Specifically, a combination of high-quality aqueous film-forming emulsion and fiber-reinforced modified gel is used to achieve the coating of more fiber-reinforced modified gel without affecting the film-forming effect and dispersibility, and a filler is added to form a combined coating, which can not only optimize the particle grading of the filler and improve the uniformity and strength of the matrix, but also can be prepared into a material that is convenient for construction and use.
[0025] (3) In the present invention, by using hydroxylated modified fibers and a specific type of modified emulsion to vacuum impregnate and gelate the silica sol, the bonding strength between the modified fibers and the aerogel matrix can be significantly improved while improving the thermal insulation performance and support strength. Specifically, after the inorganic fibers are first subjected to hydrocarbonization treatment in an acidic environment, the silicon chain hydrocarbon groups on the fiber surface can undergo hydrolysis and polymerization reactions with the silanol molecular units to generate -O-Si-O- covalent bonds, thereby improving the bonding strength between the aerogel material and other materials through covalent bonding; secondly, by introducing a surface modifier such as a silane coupling agent, the -CH3 group on the original fiber carbon chain is dehydrogenated and polymerized to generate a -CH2 flexible carbon chain, which is bonded to the -O-Si-O- bond to achieve chemical bonding between the fiber carbon chain and the aerogel matrix, further improving the bonding strength between the fiber carbon chain and the aerogel matrix, thereby macroscopically improving the thermal stability and mechanical strength of the modified silica aerogel product. DETAILED DESCRIPTION
[0026] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but those skilled in the art will appreciate that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. Those who do not specify specific conditions in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. Those who do not specify the manufacturer for reagents or instruments used are conventional products that can be purchased commercially. In addition, the terms "first", "second" and "third" are only used for descriptive purposes and cannot be interpreted as indicating or implying relative importance.
[0027] The first aspect of the present invention is to provide a method for preparing fiber-reinforced modified silica aerogel, which mainly comprises the following steps:
[0028] (1) treating the inorganic fiber with acid and performing surface modification treatment in sequence to obtain hydroxylated modified fiber;
[0029] (2) mixing silica sol, the hydroxylated modified fiber and a modified latex, and then sequentially performing vacuum impregnation treatment and gelation reaction to obtain a modified silica gel; wherein the modified latex comprises acrylic acid, an acrylate compound and a persulfate;
[0030] (3) The modified silica gel is aged and aged, and then replaced with an alcohol solution and dried to obtain a fiber-reinforced modified silica aerogel.
[0031] As a preferred embodiment, the inorganic fiber includes at least one of glass fiber, aluminum silicate fiber, basalt fiber or quartz fiber.
[0032] As a preferred embodiment, the inorganic fiber is further included in pretreatment before step (1); the pretreatment includes but is not limited to cleaning or standardized cutting of the inorganic fiber; in some optional embodiments, the cleaning of the inorganic fiber includes but is not limited to flushing, ultrasound, water washing, organic solvent washing, etc.; in some optional embodiments, the diameter of the inorganic fiber is 6μm to 15μm.
[0033] As a preferred embodiment, in step (1), the acid reagent for the acid treatment includes one of hydrochloric acid or nitric acid, and the concentration of the acid reagent is 0.5 mol / L to 2 mol / L.
[0034] As a preferred embodiment, in step (1), the duration of the acid treatment is 8h to 24h; the temperature of the acid treatment is ≥80°C, and in some more preferred embodiments, the temperature of the acid treatment is 80°C to 95°C. It can be understood that the duration is based on the contact time of the inorganic fiber in the acid reagent, and the temperature is based on the ambient temperature or the temperature of the acid reagent reached based on the environment.
[0035] As a preferred embodiment, in step (1), the modifying agent for the surface modification treatment includes at least one of γ-aminopropyltriethoxysilane (KH550), γ-(2,3-epoxypropyloxy)propyltrimethoxysilane (KH560) or an aluminate coupling agent.
[0036] As a preferred embodiment, in step (1), the surface modification treatment time is 1 h to 6 h.
[0037] As a preferred embodiment, after step (1), the hydroxylated modified fiber is further treated; the post-treatment includes but is not limited to water washing, alcohol washing, ultrasonic cleaning, drying, etc., and any of the above operations can be performed several times; in some optional embodiments, the type of alcohol used in the alcohol washing includes any one or more of methanol solution, ethanol solution, n-propanol solution or isopropanol solution, and the drying temperature is 80°C to 200°C.
[0038] As a more preferred embodiment, the post-treatment includes ultrasonic cleaning; by using ultrasonic dispersion to modify the fibers, combined with aging, seasoning, and drying in the subsequent step (3), the uniformity of the composite of fiber materials with large differences in dispersion at different scales in the gel matrix can be significantly improved, the degree of coverage of the aerogel matrix on the fiber material can be increased, and the thermal path isolation of the fiber skeleton structure can be achieved, so as to achieve the effect of improving the thermal insulation performance on a macro scale.
[0039] As a preferred embodiment, in step (2), the method for preparing the silica sol comprises: subjecting an alcohol solution of a silicon source precursor to an acid-catalyzed treatment, adjusting the pH and performing a hydrolysis reaction to obtain the silica sol.
[0040] As a more preferred embodiment, the silicon source precursor includes one or both of inorganic silicon or organic silicon; in the present invention, considering the various properties and cost of aerogel, it is preferred to use a combination of at least one inorganic silicon and at least one organic silicon as the silicon source precursor; wherein the inorganic silicon includes at least one of sodium silicate pentahydrate or water glass, and the organic silicon includes one of methyltrimethoxysilane, tetraethyl silicate, tetraethoxysilane, tetramethyl orthosilicate or tetraethyl orthosilicate.
[0041] In the present invention, an organic-inorganic composite silicon source is used to prepare aerogel. Since the composite silicon source can selectively carry flexible groups and hydrophobic groups, by appropriately adjusting the acid-base concentration, the grid skeleton strength and uniformity of the wet gel are improved when the silicon source precursor participates in the hydrolysis polymerization reaction, the impact caused by the shrinkage of the gel pores produced after drying is reduced, and the strength and toughness of the aerogel's own matrix are improved; at the same time, the inorganic silicon source, as a raw material that is easier to obtain than the organic silicon source, not only broadens the selection of aerogel preparation, but also further reduces the preparation cost, and has a good effect of taking both performance and cost into consideration.
[0042] As a more preferred embodiment, the alcohol solvent in the alcohol solution of the silicon source precursor includes but is not limited to at least one of ethanol, methanol, isopropanol or butanediol.
[0043] As a more preferred embodiment, in the alcohol solution of the silicon source precursor, the concentration of silicon dioxide is 0.24 mol / L to 0.6 mol / L; or the concentration of silicon atoms is 0.24 mol / L to 0.6 mol / L.
[0044] As an optional implementation, the method for preparing the alcohol solution of the silicon source precursor comprises: mixing the silicon source precursor with an alcohol solvent, and stirring at 300 rpm to 500 rpm for 10 min to 60 min.
[0045] As a more preferred embodiment, the acid reagent for the acid-catalyzed treatment includes at least one of oxalic acid, acetic acid, hydrochloric acid, citric acid or nitric acid.
[0046] As a more preferred embodiment, through the acid-catalyzed treatment, on the one hand, a specific solvent pH environment is achieved through the acid reagent, and on the other hand, sufficient hydrolysis is achieved through specific temperature reaction conditions; thus, the pH of the reaction solution obtained by the acid-catalyzed treatment is 2 to 4, the temperature of the acid-catalyzed treatment is 75°C to 85°C, and the time of the acid-catalyzed treatment is 2h to 10h.
[0047] As a preferred embodiment, in step (2), the amount ratio of the silica sol, the hydroxylated modified fiber and the modified latex is 1:(0.01-0.1):(0.1-1) by mass.
[0048] As a preferred embodiment, in step (2), the acrylate compound includes butyl acrylate and methyl methacrylate, and the persulfate includes at least one of sodium persulfate or potassium persulfate.
[0049] As a more preferred embodiment, in step (2), the usage ratio of acrylic acid, butyl acrylate, methyl methacrylate and persulfate is (1-10):(1-10):(5-15):(1-5) by mass.
[0050] As a preferred embodiment, in step (2), the preparation method of the modified emulsion comprises: firstly mixing the acrylate compound and the persulfate until uniform, then adding acrylic acid dropwise through a constant pressure funnel, keeping the mixture warm and standing under stirring, then filtering out insoluble matter through solid-liquid separation, and obtaining a liquid phase, which is the modified emulsion.
[0051] As a preferred embodiment, in step (2), the vacuum impregnation treatment comprises: after mixing the hydroxylated modified fiber and the modified emulsion in a closed container, evacuating the closed container to a vacuum state, and then adding the silica sol into the closed container; after the addition is completed, maintaining the vacuum state for at least 60 minutes, and then releasing the pressure to complete the vacuum impregnation treatment. In some optional embodiments, the vacuum state is based on the air pressure reaching -0.01MPa.
[0052] As a preferred embodiment, in step (2), deionized water is added to the mixture after vacuum impregnation treatment, and then the gelation reaction is carried out; wherein, the amount of deionized water added can be adjusted according to the actual mixture situation, and the specific quantitative requirements are not limited in the present invention; it can be understood that the purpose of adding deionized water is to increase the volume of the gel precursor and facilitate the subsequent gelation reaction. In some cases, deionized water may not be added. In some optional embodiments, after adding deionized water, stirring is further carried out at 50rpm to 100rpm for 20min to 40min to obtain a sol with uniform composition.
[0053] As a preferred embodiment, in step (2), the gelation reaction includes: adding an alkaline reagent to the sol obtained by the vacuum impregnation treatment; wherein the alkaline reagent includes at least one of ammonia water, sodium hydroxide or calcium hydroxide. In this step, the sol of the gel precursor is further subjected to a polycondensation reaction under alkaline conditions to complete the gelation reaction and obtain a fiber-modified silica gel.
[0054] As a more preferred embodiment, the alkaline reagent is added until the pH of the sol is 8-10.
[0055] As a preferred embodiment, in step (3), the aging includes: placing the modified silicone gel in an aging solution for natural reaction; and the aging includes: maintaining static aging at room temperature and pressure. It is understandable that the aging and aging are performed simultaneously.
[0056] As a more preferred embodiment, the aging solution comprises the following components by weight: 10 to 15 parts of trimethylchlorosilane, and one of 80 to 100 parts of n-hexane or 20 to 40 parts of tetraethyl orthosilicate.
[0057] As a more preferred embodiment, the volume ratio of the aging liquid to the modified silicone gel is (0.5-1.5):1.
[0058] As a more preferred embodiment, the aging retention time is 24h to 72h.
[0059] As a preferred embodiment, in step (3), the alcohol solute of the alcohol solution is preferably tert-butyl alcohol, the alcohol concentration of the alcohol solution is 10wt.% to 20wt.%, and the solvent of the alcohol solution is deionized water. The present invention adopts a combination of water and a specific alcohol in a specific ratio, and can achieve the replacement of wet gel by normal pressure and non-high temperature drying, without supercritical drying, high temperature and high pressure; it not only simplifies the production process, but also greatly reduces the cost.
[0060] As a preferred embodiment, in step (3), the replacement treatment includes: placing the aged and aged gel precursor in the alcohol solution, leaving it to stand for 10 to 20 hours, filtering, replacing with a new alcohol solution and repeating the above operation, and completing the replacement treatment after at least 2 replacements.
[0061] As a preferred embodiment, in step (3), the temperature of the drying treatment is 80°C to 120°C, the time of the drying treatment is 20h to 28h, and the air pressure of the drying treatment is 0 to 1MPa. In some optional embodiments, the heating rate of the drying treatment is 8°C / min to 15°C / min.
[0062] The second aspect of the present invention is to provide a fiber-reinforced modified silica aerogel; the fiber-reinforced modified silica aerogel is prepared by the preparation method of the fiber-reinforced modified silica aerogel as described in the first aspect.
[0063] The third aspect of the present invention is to provide an aerogel thermal insulation coating, wherein the aerogel thermal insulation coating comprises the fiber-reinforced modified silica aerogel as described in the second aspect.
[0064] The aerogel thermal insulation coating comprises the following components in parts by weight: 10 to 20 parts of the fiber-reinforced modified silica aerogel, 50 to 100 parts of an aqueous film-forming agent, 80 to 100 parts of a filler, 10 to 20 parts of a dispersant and 3 to 10 parts of a defoaming agent.
[0065] As an optional embodiment, the weight percentage of each component in the aerogel thermal insulation coating includes but is not limited to: the fiber reinforced modified silica aerogel 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20; the aqueous film-forming agent 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100; the filler 80, 82, 85, 88, 90, 92, 95, 98, 100; the dispersant 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20; the defoaming agent 3, 4, 5, 6, 7, 8, 9, 10; the weight percentage of each component can be any of the point values listed above, or the numerical range formed by any two of the above point values.
[0066] As a preferred embodiment, the aqueous film-forming agent includes at least one of acrylic emulsion, polyvinyl acetate emulsion, styrene-butadiene emulsion or styrene-acrylic emulsion.
[0067] As a preferred embodiment, the filler includes at least one of hollow glass microspheres, hollow ceramic floating beads, silica fume, heavy calcium carbonate, titanium dioxide, polyurethane foam or expanded polystyrene.
[0068] As a preferred embodiment, the dispersant includes at least one of sodium dodecyl sulfate, sodium polyacrylate, nonylphenol polyoxyethylene ether, sodium tripolyphosphate or tributyl phosphate.
[0069] As a preferred embodiment, the defoaming agent includes at least one of a silicone defoaming agent, an organosilicon defoaming agent or a polyether defoaming agent.
[0070] As a preferred embodiment, the aerogel thermal insulation coating comprises 0.01 to 10 parts by weight of a film-forming aid. In some optional embodiments, the amount of the film-forming aid includes but is not limited to any one of 0.01, 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or a numerical range consisting of any two of them.
[0071] As a more preferred embodiment, the film-forming aid includes at least one of calcium stearate, aluminum stearate, dialkyl methyl propionic acid, methyl ethyl ketoxime or ethylenediamine.
[0072] The fourth aspect of the present invention is to provide a method for preparing the aerogel thermal insulation coating as described in the third aspect.
[0073] The preparation method of the aerogel thermal insulation coating comprises the following steps: fully mixing the fiber-reinforced modified silica aerogel, an aqueous film-forming agent, a filler, a dispersant and a defoaming agent to obtain the aerogel thermal insulation coating.
[0074] As a preferred embodiment, after the raw material components other than the filler are fully mixed, the filler is added and further mixed to obtain the aerogel thermal insulation coating.
[0075] As a preferred embodiment, the mixing can be carried out by one or more auxiliary mixing means such as oscillation, stirring, shaking, ultrasound, centrifugation, etc., to achieve uniformity of the coating mixed phase.
[0076] The fifth aspect of the present invention is to provide the use of the aerogel thermal insulation coating as described in the third aspect in building materials. It is understood that the use includes but is not limited to a new type of building thermal insulation material, a construction method of a building thermal insulation material, a preparation method of a building thermal insulation material, etc.; when including the specific product of the aerogel thermal insulation coating, any product or method belongs to an embodiment of the use of the present invention.
[0077] It is worth noting that the aerogel thermal insulation coating described in the present invention is applied to the exterior wall of a house for thermal insulation when in use. Specifically, this type of coating is applied to the interior wall surface (generally a concrete wall surface) that has been cleaned or painted with an interface agent after cleaning, and is applied 1 to 2 times by scraping (the thickness can be selected to be 1 cm to 2 cm). After drying for 7 days, the topcoat can be rolled on this coating; only 1 to 2 times of scraping are required to achieve the construction of the thermal insulation layer and the leveling construction of the putty layer at the same time, which is simple and quick. Since the aerogel thermal insulation coating contains a coupling agent component, it will further react with the interface agent of the wall or the hydrocarbon group in the paint coating to enhance the adhesion to the substrate.
[0078] Example 1
[0079] S1: Weigh 5 g of sodium silicate pentahydrate, 10 g of water glass, and 5 g of tetramethyl orthosilicate, dissolve in 0.5 mol / L butanediol solvent (20 mL), and stir at 300 r / min for 30 min to mix the reactants evenly; then add 0.5 mol / L hydrochloric acid dropwise to adjust the pH of the sol to 2, stir evenly at 50 r / min, and let stand at room temperature for 12 h to allow the hydrolysis reaction to proceed fully to obtain silica sol.
[0080] S2: Weigh 10g of glass fiber, wash and dry it in acetone solution, and then place it in 0.5mol / L hydrochloric acid solution (20mL) at 100°C for 8h and further dry it. Then add 10mL of deionized water and 5g of γ-aminopropyltriethoxysilane solution to the treated fiber, let it stand for 2h, and then dry it at 100°C for 2h, then add methanol solution, use ultrasonic cleaning for 10min, and then further vacuum dry it at 200°C to obtain modified fiber.
[0081] S3: Weigh 5 parts of butyl acrylate, 10 parts of methyl methacrylate and 2 parts of potassium persulfate, stir them at 1000 r / min in a constant temperature water bath at 50°C until uniform, then add 5 parts of acrylic acid through a constant pressure funnel, keep warm for 1 hour and filter through a filter to obtain a modified polyacrylate emulsion.
[0082] S4: Place 5 g of modified fiber into a vacuum impregnation box in the manner of a fiber preform, and then pour 5 g of modified polyacrylate emulsion into the impregnation box and evacuate to -0.01 MPa; then gradually add 20 g of silica sol into the vacuum impregnation box; then maintain the vacuum for more than 1 hour and then slowly release the pressure, then add 10 mL of deionized water and stir at 100 r / min for 20 minutes, then drop 0.1 mol / L of ammonia water, adjust the pH of the gel solution to 10, and obtain fiber-modified silica gel.
[0083] S5: Weigh 10g of trimethylchlorosilane and 80g of n-hexane and mix them evenly, add 20g of fiber-modified silica gel thereto, and keep at room temperature for 48h. Weigh 80g of tert-butyl alcohol and 20g of deionized water and mix them evenly to prepare a replacement liquid, add it to the fiber-modified silica gel, filter the liquid once every 20h, and then add new replacement liquid. After repeating 3 times, put the obtained gel into a drying oven, heat it to 100℃ at a rate of 10℃ / min under normal pressure, and dry it for 24h to obtain the fiber-reinforced modified aerogel composite material of this embodiment.
[0084] Comparative Example 1
[0085] S1: is consistent with step S1 of embodiment 1.
[0086] S2: Weigh 10g of trimethylchlorosilane and 80g of n-hexane and mix them evenly, add 20g of silica sol prepared in S1, and keep at room temperature for 48h. Weigh 80g of tert-butyl alcohol and 20g of deionized water and mix them evenly to prepare a replacement liquid, add it to the silica sol, filter the liquid once every 20h, and then add new replacement liquid. After repeating 3 times, put the obtained gel into a drying oven, heat it to 100℃ at a rate of 10℃ / min under normal pressure, and dry it for 24h to obtain the conventional silica aerogel material of this comparative example.
[0087] Example 2
[0088] S1: Weigh 10g of methyltrimethoxysilane, 3g of water glass, and 5g of tetraethoxysilane, dissolve in 1mol / L methanol solvent (20mL), and stir at 300r / min for 30min to mix the reactants evenly. Then add 1mol / L oxalic acid dropwise to adjust the pH of the sol to 2, continue to stir evenly at 50r / min, and then stand at room temperature for 24h to allow the hydrolysis reaction to proceed fully to obtain silica sol.
[0089] S2: Weigh 20g of basalt fiber, wash and dry it in acetone solution, then place it in 0.5mol / L hydrochloric acid solution (10mL) at 80℃ for 12h and dry it. Add 10g of deionized water and 5g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane solution to the treated fiber, let it stand for 2h, and then dry it at 100℃ for 2h, then add n-propanol solution, use ultrasonic cleaning for 10min, and then further vacuum dry it at 100℃ to obtain modified basalt fiber.
[0090] S3: Weigh 5 g of butyl acrylate, 15 g of methyl methacrylate, and 1 g of potassium persulfate, stir them at 1000 r / min in a 50°C constant temperature water bath until they are uniform, then add 10 g of acrylic acid through a constant pressure funnel, keep warm for 1 hour, and filter through a filter to obtain a modified polyacrylate emulsion.
[0091] S4: 3 g of modified basalt fiber was placed in a vacuum impregnation box in the manner of a fiber preform, and then 5 g of modified polyacrylate emulsion was poured into the impregnation box and evacuated to -0.01 MPa; then 25 g of silica sol was gradually added to the vacuum impregnation box; then the vacuum was maintained for more than 1 hour and the pressure was slowly released, and then 15 mL of deionized water was added and stirred at 100 r / min for 20 minutes, and then 0.3 mol / L calcium hydroxide solution was dropped into it, and the pH of the gel solution was adjusted to 10 to obtain basalt fiber modified silica gel.
[0092] S5: Weigh 13g trimethylchlorosilane and 90g n-hexane and mix them evenly, add 25g basalt fiber modified silica gel thereto, and keep at room temperature for 48h. Weigh 60g tert-butyl alcohol and 15g deionized water and mix them evenly to prepare a replacement liquid, add it to the basalt fiber modified silica gel, filter the liquid once every 20h and then add new replacement liquid, repeat 3 times, put the obtained gel into a drying oven, heat it to 100℃ at a rate of 10℃ / min under normal pressure, and dry it for 24h to obtain the basalt fiber reinforced modified aerogel composite material of this embodiment.
[0093] Comparative Example 2
[0094] S1: is consistent with step S1 of embodiment 2.
[0095] S2: Weigh 13g of trimethylchlorosilane and 90g of n-hexane and mix them evenly, add 25g of silica sol prepared in S1, and keep at room temperature for 48h. Weigh 60g of tert-butyl alcohol and 15g of deionized water and mix them evenly to prepare a replacement liquid, add it to the silica sol, filter the liquid once every 20h, and then add new replacement liquid. After repeating 3 times, put the obtained gel into a drying oven, heat it to 100℃ at a rate of 10℃ / min under normal pressure, and dry it for 24h to obtain the conventional silica aerogel material of this comparative example.
[0096] Example 3
[0097] S1: Weigh 5g of tetraethyl silicate, 10g of water glass, and 10g of sodium silicate pentahydrate, dissolve in 1mol / L ethanol solvent (20mL), and stir at 300r / min for 30min to mix the reactants evenly. Then add 0.5mol / L citric acid dropwise to adjust the pH of the sol to 4, continue to stir evenly at 50r / min, and then stand at room temperature for 24h to allow the hydrolysis reaction to proceed fully to obtain silica sol.
[0098] S2: Weigh 15g of quartz fiber, wash and dry it in acetone solution, then place it in 0.5mol / L hydrochloric acid solution (30mL) at 80℃ for 12h and dry it. Add 10g of deionized water and 10g of aluminate coupling agent to the treated fiber, let it stand for 2h, and then dry it at 100℃ for 2h, then add isopropanol solution, use ultrasonic cleaning for 10min, and then vacuum dry it at 100℃ to obtain modified quartz fiber.
[0099] S3: Weigh 10 g of butyl acrylate, 10 g of methyl methacrylate, and 5 g of potassium persulfate, stir at 60°C and 1000 r / min until uniform, then add 10 g of acrylic acid through a constant pressure funnel, keep warm for 1 hour, and filter through a filter to obtain a modified polyacrylate emulsion.
[0100] S4: 5 g of modified quartz fiber is placed in a vacuum impregnation box in the form of a preform, and then 3 g of modified polyacrylate emulsion is poured into the impregnation box and evacuated to -0.01 MPa; then 25 g of silica sol is gradually added to the vacuum impregnation box; then the vacuum is maintained for more than 1 hour and the pressure is slowly released, 15 mL of deionized water is added and stirred at 100 r / min for 20 minutes, and then 0.1 mol / L sodium hydroxide solution is dropped into it, and the pH of the gel solution is adjusted to 8 to obtain quartz fiber modified silica gel.
[0101] S5: Weigh 10g of trimethylchlorosilane and 80g of n-hexane and mix them evenly, add 25g of quartz fiber modified silica gel thereto, and keep at room temperature for 48h. Weigh 100g of tert-butyl alcohol and 30g of deionized water and mix them evenly to form a replacement liquid, add it to the quartz fiber modified silica gel, filter the liquid once every 20h and then add new replacement liquid, repeat 4 times, put the obtained gel into a drying oven, heat it to 100℃ at a rate of 10℃ / min under normal pressure, and dry it for 24h to obtain the quartz fiber reinforced modified aerogel composite material of this embodiment.
[0102] Comparative Example 3
[0103] S1: is consistent with step S1 of embodiment 3.
[0104] S2: Weigh 10g of trimethylchlorosilane and 80g of n-hexane and mix them evenly, add 25g of silica sol prepared in S1, and keep at room temperature for 48h. Weigh 100g of tert-butyl alcohol and 30g of deionized water and mix them evenly to prepare a replacement liquid, add it to the silica sol, filter the liquid once every 20h, and then add new replacement liquid. After repeating 4 times, put the obtained gel into a drying oven, heat it to 100℃ at a rate of 10℃ / min under normal pressure, and dry it for 24h to obtain the conventional silica aerogel material of this comparative example.
[0105] Table 1 provides a performance comparison of the fiber-reinforced modified silica aerogels obtained in Examples 1 to 3 and Comparative Examples 1 to 3 and the conventional control silica aerogels. The thermal conductivity is tested based on the thermal conductivity of the wet modified aerogel composite material before being placed in a drying oven for drying in step S5 of each example and comparative example; and the tap density and nitrogen adsorption specific surface area are tested based on the powdered modified aerogel composite material obtained after drying in step S5.
[0106] Table 1
[0107]
[0108]
[0109] Example 4
[0110] Weigh 50 parts of styrene-butadiene emulsion, 2 parts of calcium stearate, 6 parts of silicone defoamer and 6 parts of sodium lauryl sulfate, stir at 200 r / min for 10 minutes to mix evenly to prepare an aqueous film-forming emulsion.
[0111] Weigh 10 parts of the fiber-reinforced modified aerogel prepared in Example 1, 30 parts of hollow glass microspheres, 5 parts of heavy calcium carbonate powder, 3 parts of titanium dioxide, and 10 parts of polyurethane foam, mix them evenly, and then slowly add the aqueous film-forming emulsion at a speed of 50 r / min to prepare the thermal insulation coating composition of this example.
[0112] Example 5
[0113] It is basically the same as Example 4, except that the fiber-reinforced modified aerogel prepared in Example 1 is replaced by the fiber-reinforced modified aerogel prepared in Example 2.
[0114] Example 6
[0115] It is basically the same as Example 4, except that the fiber-reinforced modified aerogel prepared in Example 1 is replaced by the fiber-reinforced modified aerogel prepared in Example 3.
[0116] Example 7
[0117] Weigh 70 parts of styrene acrylic emulsion, 10 parts of acrylic emulsion, 5 parts of ethylenediamine, 3 parts of polyether defoaming agent and 10 parts of sodium dodecyl sulfate, stir at 200 r / min for 20 minutes to mix evenly to prepare an aqueous film-forming emulsion.
[0118] Weigh 20 parts of the fiber-reinforced modified aerogel prepared in Example 1, 40 parts of hollow glass microspheres, 10 parts of hollow ceramic beads, 3 parts of heavy calcium powder, and 10 parts of titanium dioxide, mix them evenly, and then slowly add the aqueous film-forming emulsion at a speed of 50 r / min to prepare the thermal insulation coating composition of this example.
[0119] Example 8
[0120] It is basically the same as Example 7, except that the fiber-reinforced modified aerogel prepared in Example 1 is replaced by the fiber-reinforced modified aerogel prepared in Example 2.
[0121] Example 9
[0122] It is basically the same as Example 7, except that the fiber-reinforced modified aerogel prepared in Example 1 is replaced by the fiber-reinforced modified aerogel prepared in Example 3.
[0123] Example 10
[0124] 70 parts of styrene-butadiene emulsion, 10 parts of dimethyl propionic acid, 5 parts of silicone defoamer and 5 parts of nonylphenol polyoxyethylene ether were weighed and stirred at 200 r / min for 20 minutes to mix evenly to prepare an aqueous film-forming emulsion.
[0125] Weigh 30 parts of the fiber-reinforced modified aerogel prepared in Example 1, 50 parts of hollow glass microspheres, 5 parts of hollow ceramic beads, 5 parts of expanded polystyrene, 10 parts of titanium dioxide, and 5 parts of silica fume, mix them evenly, and then slowly add the aqueous film-forming emulsion at a speed of 50 r / min to prepare the thermal insulation coating composition of this example.
[0126] Embodiment 11
[0127] It is basically the same as Example 10, except that the fiber-reinforced modified aerogel prepared in Example 1 is replaced by the fiber-reinforced modified aerogel prepared in Example 2.
[0128] Example 12
[0129] It is basically the same as Example 10, except that the fiber-reinforced modified aerogel prepared in Example 1 is replaced by the fiber-reinforced modified aerogel prepared in Example 3.
[0130] Comparative Example 4
[0131] Weigh 50 parts of styrene-butadiene emulsion, 2 parts of calcium stearate, 6 parts of silicone defoamer and 6 parts of sodium lauryl sulfate, stir at 200 r / min for 10 min to mix evenly to prepare an aqueous film-forming emulsion (this aqueous film-forming emulsion is the same as that in Example 4).
[0132] 10 parts of conventional silica aerogel prepared in Comparative Example 1, 60 parts of hollow glass microspheres and 10 parts of polyurethane foam were mixed evenly and then slowly added into 80 parts of aqueous film-forming emulsion at a speed of 50 r / min to prepare a silica aerogel thermal insulation coating.
[0133] Comparative Example 5
[0134] Weigh 50 parts of styrene-butadiene emulsion, 2 parts of calcium stearate, 6 parts of silicone defoamer and 6 parts of sodium lauryl sulfate, stir at 200 r / min for 10 min to mix evenly to prepare an aqueous film-forming emulsion (this aqueous film-forming emulsion is the same as that in Example 4).
[0135] 60 parts of hollow glass microspheres and 10 parts of polyurethane foams were uniformly mixed and then slowly added into 60 parts of aqueous film-forming emulsion at a speed of 50 r / min to prepare a thermal insulation coating.
[0136] Test example
[0137] The thermal insulation coatings prepared in Examples 4 to 12 and Comparative Examples 4 to 5 were tested for performance. The crack resistance was tested according to method 6.8 of JG / T 24-2000; the polishability, construction performance, and bonding strength were tested according to the requirements of JG / T298-2010; the drying time was tested according to the provisions of method B of GB / T1728-1989; the thermal conductivity was tested according to the requirements of GB / T10294-2008; and the combustion grade was tested according to the test method specified in GB / T 5464-2010. Table 2 shows the performance results of each thermal insulation coating.
[0138] Table 2
[0139]
[0140]
[0141] According to the above Table 1, it can be seen that the thermal insulation performance of the fiber-reinforced modified aerogel composite thermal insulation coating prepared according to the present invention is much higher than that of traditional thermal insulation materials, and is easy to construct and use.
[0142] Based on the comparison of the data results of the embodiments, within a certain range, the higher the dosage of fiber-reinforced modified aerogel, the better the thermal insulation effect, but the bonding strength also shows a more obvious decrease, but it is still higher than the bonding strength of the current thermal insulation mortar. As can be seen from Comparative Example 4, although there is no significant difference in its thermal insulation performance, the bonding strength of the coating with fiber-reinforced modified aerogel added is much higher than that of the untreated aerogel coating, proving that fiber reinforcement and modification have a good enhancement on the aerogel matrix. As can be seen from Comparative Example 5, since no aerogel component is added, its thermal insulation performance is significantly different from that of the embodiments, and the fire retardant performance is further reduced. It can be seen that the addition of aerogel can not only improve the thermal insulation performance, but also have a certain effect in fire retardant.
[0143] In summary, the fiber-reinforced modified aerogel prepared by the present invention and the aerogel thermal insulation coating prepared therefrom fully consider the thermal insulation performance requirements and construction convenience of the internal insulation of the building exterior wall, and achieve an ideal comprehensive performance effect.
[0144] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A method for preparing fiber-reinforced modified silica aerogel, characterized in that: The steps include: (1) treating the inorganic fiber with acid and performing surface modification treatment in sequence to obtain hydroxylated modified fiber; (2) mixing silica sol, the hydroxylated modified fiber and a modified emulsion, and then sequentially performing vacuum impregnation treatment and gelation reaction to obtain a modified silica gel; wherein the modified emulsion comprises acrylic acid, an acrylate compound and a persulfate; (3) The modified silica gel is aged and aged, and then replaced with an alcohol solution and dried to obtain a fiber-reinforced modified silica aerogel.
2. The method for preparing fiber-reinforced modified silica aerogel according to claim 1, characterized in that: In step (1), at least one of the following features (a) to (d) is included: (a) the inorganic fiber comprises at least one of glass fiber, aluminum silicate fiber, basalt fiber or quartz fiber; (b) the acid treatment time is 8h to 24h, and the acid treatment temperature is ≥80°C; (c) the concentration of the acid reagent for the acid treatment is 0.5 mol / L to 2 mol / L; (d) The modifying agent for the surface modification treatment includes at least one of γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane or an aluminate coupling agent.
3. The method for preparing fiber-reinforced modified silica aerogel according to claim 1, characterized in that: The preparation method of the silica sol comprises: preparing an alcohol solution of a silicon source precursor and performing an acid catalytic treatment; Preferably, the silicon source precursor includes at least one inorganic silicon and at least one organic silicon; the inorganic silicon includes at least one of sodium silicate pentahydrate or water glass, and the organic silicon includes at least one of methyltrimethoxysilane, tetraethyl silicate, tetraethoxysilane, tetramethyl orthosilicate or tetraethyl orthosilicate.
4. The method for preparing fiber-reinforced modified silica aerogel according to claim 1, characterized in that: In the modified emulsion, the acrylate compound includes butyl acrylate and methyl methacrylate, and the persulfate includes at least one of sodium persulfate or potassium persulfate; Preferably, in the modified emulsion, the mass ratio of the acrylic acid, the butyl acrylate, the methyl methacrylate and the persulfate is (1-10): (1-10): (5-15): (1-5); Preferably, the mass ratio of the silica sol, the hydroxylated modified fiber and the modified latex is 1:(0.01-0.1):(0.1-1).
5. The method for preparing fiber-reinforced modified silica aerogel according to claim 1, characterized in that: In steps (2) to (3), at least one of the following features (A) to (D) is included: (A) The vacuum impregnation treatment comprises: evacuating a closed container containing the hydroxylated modified fiber and the modified emulsion to a vacuum state, and then adding the silica sol; maintaining the vacuum state for at least 60 minutes, and then releasing the pressure to obtain a gel precursor; (B) the gelation reaction comprises: adding an alkali reagent to the solution of the gel precursor obtained after the vacuum impregnation treatment until the pH of the sol solution is 8 to 10; (C) The aging solution used in the aging process comprises the following components by weight: 10 to 15 parts of trimethylchlorosilane and one of 80 to 100 parts of n-hexane or 20 to 40 parts of tetraethyl orthosilicate; (D) The aging maintenance time is 24h to 72h.
6. A fiber-reinforced modified silica aerogel, characterized in that: The aerogel is prepared by the method for preparing the fiber-reinforced modified silica aerogel as claimed in any one of claims 1 to 5.
7. An aerogel thermal insulation coating, characterized in that: Comprising the fiber-reinforced modified silica aerogel as claimed in claim 6; Preferably, the aerogel thermal insulation coating comprises the following components in parts by weight: 10 to 20 parts of the fiber-reinforced modified silica aerogel, 50 to 100 parts of an aqueous film-forming agent, 80 to 100 parts of a filler, 10 to 20 parts of a dispersant and 3 to 10 parts of a defoaming agent.
8. The aerogel thermal insulation coating according to claim 7, characterized in that: It includes at least one of the following features (I) to (V): (I) the aqueous film-forming agent comprises at least one of acrylic emulsion, polyvinyl acetate emulsion, styrene-butadiene emulsion or styrene-acrylic emulsion; (II) The filler comprises at least one of hollow glass microspheres, hollow ceramic beads, silica fume, heavy calcium carbonate, titanium dioxide, polyurethane foam or expanded polystyrene; (III) the dispersant comprises at least one of sodium lauryl sulfate, sodium polyacrylate, nonylphenol polyoxyethylene ether, sodium tripolyphosphate or tributyl phosphate; (IV) the defoamer comprises at least one of a silicone defoamer, an organosilicon defoamer or a polyether defoamer; (V) The aerogel thermal insulation coating further comprises 0.01 to 10 parts by weight of a film-forming aid; the film-forming aid comprises at least one of calcium stearate, aluminum stearate, dialkyl methyl propionic acid, methyl ethyl ketoxime or ethylenediamine.
9. The method for preparing the aerogel thermal insulation coating according to claim 7 or 8, characterized in that: The steps include: The fiber-reinforced modified silica aerogel, aqueous film-forming agent, filler, dispersant and defoamer are fully mixed to obtain the aerogel thermal insulation coating.
10. Use of the aerogel thermal insulation coating according to claim 7 or 8 in building materials.
Citation Information
Cited By
Aerogel thermal insulation coating and preparation method thereof
CN120059548A